Fungal Metabolites - Mérillon, Jean-Michel; Ramawat, Kishan Gopal (Reference Series in Phytochemistry, 2017)
This handbook compiles authoritative information about fungal metabolites and their chemistry and biotechnology. The first in the reference work series "Phytochemicals", and written by a team of international expert authors, this book provides reference information ranging from the description of fungal natural products, over their use e.g. as anticancer agents, to microbial synthesis, even spanning to the production of secondary metabolites on industrial scale. On the other hand it also describes global health issues related to aflatoxin production in foods and agriculture, including perspectives for detoxification. The handbook characterizes different compound classes derived from fungal secondary metabolites, like ergot alkaloids and aflatoxins. The discussion puts a special emphasis on how potentially useful compounds can be obtained and what applications they can find, on the one hand, and how potential dangers can be encountered on the other hand. The comprehensive chapters in this handbook will thus appeal to readers from diverse backgrounds in chemistry, biology, life sciences, and even medicine, who are working or planning to work with fungal (secondary) metabolites and their application. They provide the readers with rich sources of reference information on important topics in this field.- Resumé vydavatel